Rhamnogalacturonan-I as a nematode chemoattractant from Lotus corniculatus L. super-growing root culture - Oota, Morihiro; Toyoda, Syuuto; Kotake, Toshihisa; Wada, Naoki; Hashiguchi, Masatsugu; Akashi, Ryo; Ishikawa, Hayato; Favery, Bruno; Tsai, Allen Yi-Lun; Sawa, Shinichiro (Frontiers in Plant Science, 2023)
The soil houses a tremendous amount of micro-organisms, many of which are plant parasites and pathogens by feeding off plant roots for sustenance. Such root pathogens and parasites often rely on plant-secreted signaling molecules in the rhizosphere as host guidance cues. Here we describe the isolation and characterization of a chemo-attractant of plant-parasitic root-knot nematodes (Meloidogyne incognita, RKN). The Super-growing Root (SR) culture, consisting of excised roots from the legume species Lotus corniculatus L., was found to strongly attract infective RKN juveniles and actively secrete chemo-attractants into the liquid culture media. The chemo-attractant in the culture media supernatant was purified using hydrophobicity and anion exchange chromatography, and found to be enriched in carbohydrates. Monosaccharide analyses suggest the chemo-attractant contains a wide array of sugars, but is enriched in arabinose, galactose and galacturonic acid. This purified chemo-attractant was shown to contain pectin, specifically anti-rhamnogalacturonan-I and anti-arabinogalactan protein epitopes but not anti-homogalacturonan epitopes. More importantly, the arabinose and galactose sidechain groups were found to be essential for RKN-attracting activities. This chemo-attractant appears to be specific to M. incognita, as it wasn’t effective in attracting other Meloidogyne species nor Caenorhabditis elegans. This is the first report to identify the nematode attractant purified from root exudate of L corniculatus L. Our findings re-enforce pectic carbohydrates as important chemicals mediating micro-organism chemotaxis in the soil, and also highlight the unexpected utilities of the SR culture system in root pathogen research.